Exploring learning outcomes in an engineering programme - Flores Delgadillo, Will Johnny; López Poveda, Anayanci (Nexo Revista Científica, 2022)
The paper is focused on identifying the development level of learning outcomes related to courses in an undergraduate engineering programme in Nicaragua from teacher and student perspectives. This is an explorative case study research based on curriculum model of Computer engineering of IEEE/ACM. We determine the contrasting level of learning outcomes between teacher and student perspectives.